Running economy in long-distance runners is positively affected by running experience and negatively by aging - Dos Anjos Souza, V. R.; Seffrin, A.; Alves da Cunha, R.; Vivan, L.; Barbosa de Lira, C. A.; Vancini, R. L.; Weiss, K.; Knechtle, B.; Santos Andrade, M. (Physiology & Behavior, 2022)
Introduction: The maximum oxygen uptake (VO2max), the maximum rate of oxygen that can be sustained before the onset of blood lactate accumulation, and the metabolic cost of locomotion are the main physiological factors associated with long-distance running performance. The latter is known as the running economy. Generally, runners reach peak performance in long races between 25 and 30 years of age, with a progressive decline occurring thereafter. However, it is not known whether the running economy is affected or how it is affected by aging.